A 220 GHz frequency tripler based on 3D electromagnetic model of the schottky diode and the field‐circuit co‐simulation method. Issue 7 (23rd April 2016) - Zhang, Yong; Zhong, Wei; Ren, Tianhao; Chen, Yapei; Yan, Bo; Xu, Ruimin
ABSTRACT: In this article, a 220 GHz frequency tripler using three‐dimensional (3D) electromagnetic simulation is designed. Due to the characteristics of extremely short working wavelength and ultra‐small circuit size of terahertz frequency multipliers, complicated parasitic effect cannot be ignored, which leads to a limited optimization space for circuit matching in the design of terahertz components. In this article, a precise 3D electromagnetic (EM) model of the planar Schottky barrier diode (SBD) is established and the field‐circuit co‐simulation method is proposed for the design of the 220 GHz tripler. Compared with the varistor diode, the frequency multiplier based on the varactor diode will produce higher output power due to its lossless mechanism. The measured results show that the output power is higher than 5 mW in the frequency range 220∼228 GHz, with the maximum output power of 6.34 mW. Typical conversion loss is 15 dB in the frequency range 216∼232 GHz. The frequency tripler has the characteristics of compact size, low loss, and high output power. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:1647–1651, 2016